2017
DOI: 10.1016/j.cels.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Investigation of Multi-TLR Sensing Identifies Regulators of Sustained Gene Activation in Macrophages

Abstract: SUMMARY A typical pathogen presents a combination of Toll-like receptor (TLR) ligands during infection. Although individual TLR pathways have been well characterized, the nature of this “combinatorial code” in pathogen sensing remains unclear. Here, we conducted a comprehensive transcriptomic analysis of primary macrophages stimulated with all possible pairwise combinations of four different TLR ligands to understand the requirements, kinetics, and outcome of combined pathway engagement. We find that signal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 46 publications
4
47
0
Order By: Relevance
“…To evaluate these differences in our model system, we stimulated BMM with PIC (10ng/ml and 10μg/ml) or LPS (100ng/ml) for 18 hours and assessed inflammatory (TNF-α, IL-1β, and IL-6) and antiviral (IFN-α, IFN-β and CXCL10) cytokine production in culture supernatants. PIC concentrations were selected to emulate responses in early (low levels of virus) and late stages of infection (high levels of virus), where Lin et al found that only high (≥ 10μg/ml) concentrations of PIC can induce robust inflammatory cytokine production 34 . The LPS concentration was selected based on its ability to repurpose mitochondrial function to support ROS production 15 .…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate these differences in our model system, we stimulated BMM with PIC (10ng/ml and 10μg/ml) or LPS (100ng/ml) for 18 hours and assessed inflammatory (TNF-α, IL-1β, and IL-6) and antiviral (IFN-α, IFN-β and CXCL10) cytokine production in culture supernatants. PIC concentrations were selected to emulate responses in early (low levels of virus) and late stages of infection (high levels of virus), where Lin et al found that only high (≥ 10μg/ml) concentrations of PIC can induce robust inflammatory cytokine production 34 . The LPS concentration was selected based on its ability to repurpose mitochondrial function to support ROS production 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, during TLR signaling it is unlikely that only a specific receptor type is activated, given that pathogens will produce a variety of activating ligands. It has been shown that TLR pathway crosstalk enhances cytokine secretion (Lin et al, 2017) and thus different TLR types localized in the same compartment-for example, plasma membrane-bound TLR4 and TLR1/2, which respond to bacterial lipopolysaccharide and lipopeptide-could act synergistically. Whether the TIR domains of hMyD88 from one Myddosome are able to simultaneously interact with the receptor TIR dimer or the MAL-TIR/receptor TIR tetramer from two different TLR receptor types, while plausible, is currently not known.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular details of PRR signaling pathways have been predominantly derived from studies that involve stimulation of single PRRs by their cognate ligands (Alexopoulou et al, 2001;Brown et al, 2002;Fitzgerald et al, 2001;Gottar et al, 2002;Hemmi et al, 2000;Horng et al, 2002;Jurk et al, 2002;McCoy and O'Neill, 2008;Shimazu et al, 1999;Takeuchi et al, 2001;Takeuchi et al, 2002;Watson et al, 1977;Wright et al, 1990;Wright et al, 1989). While these studies have revealed that there are common frameworks for organization of the PRR pathways, few have addressed how simultaneously activated PRR pathways interact to ensure an appropriate host response to the combined PAMP and/or DAMP signals encountered during microbial infection or tissue damage (Bagchi et al, 2007;Gottschalk et al, 2019;Lin et al, 2017;Liu et al, 2015;Napolitani et al, 2005; Suet Ting Tan et al, 2013;Tan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%